Tongue Base Schwannoma: A Case Report and Literature Review - Ahmed, Nagwa Abd El-Sadek (Asian Pacific Journal of Cancer Biology, 2023)
Background: Schwannoma is a benign tumor arises from Schwann cells of the peripheral nerves. Tongue base schwannomas are very rare and have been sporadically reported; it is usually missed when evaluating a tongue base mass. This work aimed to report a new case of tongue base schwannoma and to review the literature about this tumor. Case presentation: A male patient of 40 years old presented with slowly enlarging mass at the tongue base. Clinical and radiological findings highly suspected of tongue base benign lesion. Trans-oral resection was done and the specimen was subjected to the histopathological evaluation. Conclusion: Schwannoma should be considered for a well-defined, painless, firm swelling at the tongue base.